Working from home around the world - Cevat Giray Aksoy; Jose Maria Barrerro; Nicholas Bloom; Steven J. Davis; Mathias Dolls; Pablo Zarate (EconPol Forum, 2022)
Most workers were favorably surprised by their productivity in work from home (WFH) mode during the pandemic. Employer plans for WFH levels after the pandemic rise strongly with these individual-level productivity surprises. Planned WFH levels also rise with the cumulative stringency of government-mandated lockdowns during the pandemic. ¦ Employees value the option to WFH 2-3 days per week at 5 percent of pay, on average, with higher valuations for women, people with children, highly-educated workers, and those with longer commutes.
Keywords: 330; Coronavirus; Telearbeit; Welt